Impact of Endoscopic Ultrasound in Evaluation of Upper Abdominal Pain (Medicine Today, 2021)
Introduction: Upper abdominal pain is found to be one of the most common presenting symptoms. Endoscopic ultrasound may be a useful tool to yield a specific diagnosis. Aim of our study was to find the etiology of upper abdominal pain with normal endoscopic findings and compare the findings of endoscopic ultrasound with those of trans-abdominal ultrasound.Materials and Methods: This was a cross sectional study conducted in the department of gastroenterology, Sir Salimullah Medical College from January 2015 to December 2019. Total 238 patients suffering from upper abdominal pain who previously underwent endoscopy with normal results and trans abdominal ultrasound with doubtful findings were enrolled in this study. All patients were evaluated properly with history, clinical examination and relevant blood investigations. Then the patients underwent endoscopic ultrasound with conscious sedation. Computed tomorgraphy, magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography were done in cases where needed and correlated with endoscopic ultrasound results.Results: Among the total 238 patients, 137 were male and 101 were female. Most predominant age range was 31-40 years. Pain was moderate in severity in 43.27%, epigastric pain was in 59.66% and pain referred to back was in 37.39% patients. Comparison with trans abdominal ultrasound regarding etiologies of upper abdominal pain was statistically significant (P=0.000). Comparative analysis between the two modalities regarding gall bladder, common bile duct, pancreas were also found significant with P values of 0.040, 0.005, 0.000 respectively. Forty two patients were diagnosed as chronic pancreatitis based on Rosemont criteria by endoscopic ultrasound.Conclusion: Endoscopic ultrasound is a modern diagnostic tool which can detect hepato-pancreato-biliary pathologies and also mucosal irregularities of stomach and esophagus. So, it can be considered as a first line investigation to diagnose the underlying etiology of upper abdominal pain.Medicine Today 2021 Vol.33(1): 1-6